Efficacy and Safety of Trabectome Surgery in Chinese Open-Angle Glaucoma. Issue 15 (April 2016) - Lee, Jacky W.Y.; Yick, Doris W.F.; Tsang, Susanna; Yuen, Can Y.F.; Lai, Jimmy S.M.
Abstract : Abstract: To investigate the clinical outcome of the Trabectome in Chinese open-angle glaucoma (OAG). This prospective case series recruited pseudophakic glaucoma subjects with open-angle configuration. Trabeculectomy ab interno was performed using the Trabectome to 120° of the trabecular meshwork. Intraocular pressure (IOP) and medications were recorded preoperatively and every 3 months postoperatively. Visual acuity was measured preoperatively and at 1 and 6 months postoperatively. One-way ANOVA with Tukey Multiple Comparison Test were used to measure the pre and postoperative parameters. In 19 eyes of 19 Chinese subjects, 26.3% were uveitic, 68.4% were primary open-angle glaucoma, and 5.3% had a history of chronic angle-closure glaucoma with open-angles after cataract extraction. The subjects' mean age was 67.5 ± 14.4 years, with 4 females and 15 males. Two patients required secondary filtration procedure. At 6 months, the IOP reduced by 34.8% (24.4 ± 4.4 mm Hg to 15.9 ± 5.1 mm Hg, P  < 0.0001). The number of types of antiglaucoma medications was reduced by 28.2% (3.9 ± 0.8–2.8 ± 1.6, P  < 0.0001). The visual acuity was static at 1 and 6 months postoperatively ( P  = 0.4). There were no intraoperative complications. 26.3% of subjects had a transient IOP spike > 21 mm Hg, 1 had hyphema requiring washout, and 1 had reactivation of herpetic keratitis. The success rate at 6 months was 89.5%. Trabectome achieved a modest reduction in IOP and medications in the majority of pseudophakic Chinese OAG eyes.